2020
DOI: 10.1212/nxg.0000000000000513
|View full text |Cite
|
Sign up to set email alerts
|

Manifesting carriers of X-linked myotubular myopathy

Abstract: ObjectiveTo analyze the modulation of the phenotype in manifesting carriers of recessive X-linked myotubular myopathy (XLMTM), searching for possible genetic modifiers.MethodsTwelve Brazilian families with XLMTM were molecularly and clinically evaluated. In 2 families, 4 of 6 and 2 of 5 manifesting female carriers were identified. These females were studied for X chromosome inactivation. In addition, whole-exome sequencing was performed, looking for possible modifier variants. We also determined the penetrance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…For example, inherited myopathies, including GNEM, can manifest with intrafamilial variability in regard to clinical phenotype, age of onset, or disease progression 29 31 . In addition, there is evidence of genetic modifiers accompanying the primary mutation or modulating the phenotype 32 , 33 . Therefore, a model system able to capture gene variability while also recapitulating the key pathological characteristics becomes crucial for elucidating yet-to-be discovered contributors to disease etiology.…”
Section: Discussionmentioning
confidence: 99%
“…For example, inherited myopathies, including GNEM, can manifest with intrafamilial variability in regard to clinical phenotype, age of onset, or disease progression 29 31 . In addition, there is evidence of genetic modifiers accompanying the primary mutation or modulating the phenotype 32 , 33 . Therefore, a model system able to capture gene variability while also recapitulating the key pathological characteristics becomes crucial for elucidating yet-to-be discovered contributors to disease etiology.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous literature suggests that these mechanisms on their own cannot explain the phenotype in all carriers and that additional disease-modifying factors very likely exist. 14,15,18 For example, a recent article by Souza et al 17 has suggested killer cell immunoglobulin-like receptor mutations as genetic modifiers in manifesting XL-MTM carriers, with a potentially protective role suggested by their presence in nonmanifesting carriers and their absence in manifesting carriers.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Manifestations in these carriers may be due to skewed X-chromosomal inactivation or other X-chromosomal alterations, but additional modifiers have also been considered. 10,12,15,17 There is probably a reporting bias in the literature toward the most severely affected carriers. 9,12,14 Symptoms in XL-MTM carriers have recently been systematically investigated in 2 large cohorts.…”
mentioning
confidence: 99%
“…For example, inherited myopathies, including GNE myopathy, can manifest with intrafamilial variability in regard to clinical phenotype, age of onset, or disease progression (Dotti et al, 2018;Stober et al, 2010;Diniz et al, 2016). In addition, there is evidence of genetic modifiers, accompanying the primary mutation, modulating the phenotype (Bello et al, 2016;Souza et al, 2020). Therefore, a model system able to capture gene variability while also recapitulating the key pathological characteristics becomes crucial for elucidating yet-to-be discovered contributors to disease etiology.…”
Section: Discussionmentioning
confidence: 99%